PENGARUH MOTIVASI, LINGKUNGAN KERJA DAN KOMPETENSI TERHADAP KINERJA KARYAWAN PADA PT. ANGKASA PURA II (PERSERO) KANTOR CABANG KUALANAMU - Bambang Nugroho; Imarlia Ginting; Sri Wanti Nasution; Eva Susanti; Ummy Syahti (Jurnal Prodi Fakultas Ekonomi-UISU, 2021)
Optimal performance on each employee will affect the company's activities where it is expected by the company that employees must always improve their performance for the benefit and benefit of the company. Many factors can determine the ups and downs of the performance of employees in each company. These factors include the things that influence motivation of employees, the existence of a comfortable work environment and training related to employee competence. The purpose of this study was to determine the effect of motivation, work environment and competence on employee performance at PT. Angkasa Pura II (Persero) Kualanamu Branch Office. This study uses an associative approach, namely research conducted to determine the effect or relationship between the independent variables with the dependent variable. The results showed that partial motivation did not have a significant effect on employee performance. Partially work environment has a significant effect on employee performance. Partially competence have a significant effect on employee performance. Simultaneously motivation, work environment and competence have a significant effect on performance. Obtained the results of the coefficient of determination is worth 0.825 or 82.5% meaning that around 82.5% of the performance variable can be explained by the motivation variable, work environment and competence. Or it can be said that the contribution of motivation, work environment and competence to employee performance at PT. Angkasa Pura II (Persero) Kualanamu Branch Office is 82.5%. The remaining 17.5% is influenced by variables not examined in this study.